Monitoring phthalates in table and fortified wines by headspace solid-phase microextraction combined with gas chromatography–mass spectrometry analysis - Perestrelo, Rosa (2022)
Phthalates are a class of endocrine disruptors extensively used in plastic production as plasticizers, and as a result, they can be found in foods as a result of their migration ability. The occurrence of phthalates was monitored in 20 Portuguese wines using a simple, reliable, and environmentally friendly analytical method, headspace solid-phase microextraction combined with gas chromatography−mass spectrometry. Satisfactory figures of merit of method, linearity (correlation coefficient of ≥0.992), recovery (80.3−107.6%), precision (relative standard deviation of <13%), and limits of detection (0.03−0.11 μg/L) and quantification (0.09−0.36 μg/L) were achieved. Dibutyl phthalate and di-n-octyl phthalate were found in measurable quantities in table and fortified wines. The obtained results revealed that these wines do not represent any concern for human exposure, because their concentrations were lower than the tolerable daily intakes established by the European Food Safety Authority.